Mini-invasive foam sclerotherapy-assisted ligation versus surgical flush ligation for incompetent sapheno-popliteal junction treatment. (October 2019) - Gianesini, Sergio; Menegatti, Erica; Sibilla, Maria Grazia; Neuhardt, Diana; Maietti, Elisa; Tessari, Mirko; Zamboni, Paolo
Objectives: Comparison of a flush sapheno-popliteal junction ligation versus a mini-invasive foam sclerotherapy-assisted ligation. Methods: Forty-eight chronic venous disease patients underwent sapheno-popliteal junction flush ligation (group A). Forty-one patients underwent small saphenous vein ligation by means of mini-invasive incision with foam sclerotherapy of the popliteal stump (group B). Results: At 4.1 ± 3.3 years mean follow-up, sapheno-popliteal junction recurrence was detected in four patients of group A (4/48; 8.3%) and in two cases of group B (3/41; 7.3%) ( P = ns ). Mean procedural time was 36 ± 11 minutes versus 21 ± 6 minutes ( p <0.0001). A mild post-operative paresthesia lasting more than 24 h was reported in 6.3% (3/48) of group A versus 2.4% (1/41) ( p <0.009) of group B. At one-year check-up, Aberdeen Varicose Vein Questionnaire significantly improved in both groups with no significant difference between group A and B. Conclusions: Foam-assisted mini-invasive sapheno-popliteal ligation represents a time and clinical-effective option, associated with a decrease in post-operative paresthesia risk.